2007
DOI: 10.1002/ffj.1790
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of volatile compounds in selected citrus fruits from Asia. Part I: freshly‐squeezed juice

Abstract: The volatile compounds in three selected citrus fruits from Asia, Indonesian Pontianak orange (Citrus nobilis Lour. var. microcarpa Hassk.), Indian Mosambi (Citrus sinensis Osbeck) and Philippine Dalandan (Citrus reticulata Blanco), were characterized. The volatile compounds from the headspace of the citrus juices were isolated by solid-phase microextraction (SPME) prior to separation with gas chromatograph (GC) and identification by mass spectrometry (MS). The volatile compounds of the juices were extracted b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 21 publications
2
39
0
Order By: Relevance
“…In fact, the composition of the oil is significantly affected by the ripeness of fruits, vegetative stage of plant, storage condition and extraction method (Njoroge, Mungal, Koaze, Phi, & Sawamura, 2006;Venkateshwarlu & Selvaraj, 2000). The quality and the odor of the oil are influenced by the limonene content which may vary in the different agro-climatic conditions (Dharmawan et al, 2007). Significant contributions were made on the composition of C. reticulata EO (Shaw, 1979;Slater, 1961).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In fact, the composition of the oil is significantly affected by the ripeness of fruits, vegetative stage of plant, storage condition and extraction method (Njoroge, Mungal, Koaze, Phi, & Sawamura, 2006;Venkateshwarlu & Selvaraj, 2000). The quality and the odor of the oil are influenced by the limonene content which may vary in the different agro-climatic conditions (Dharmawan et al, 2007). Significant contributions were made on the composition of C. reticulata EO (Shaw, 1979;Slater, 1961).…”
Section: Introductionmentioning
confidence: 97%
“…Lime flavours are used in beverage, confectionary, cookies and desserts (Buchel, 1989;Dharmawan, Kasapis, Curran, & Johnson, 2007). The exocarp of C. reticulata and Citrus sinensis is used for flavorings of liquor.…”
Section: Introductionmentioning
confidence: 99%
“…Ethanol (94110 ng/mL), followed by limonene (34516 ng/mL), were always the major components identified by HS-SPME/GC/ MS from the Spanish Hernandina mandarin variety (Peréz et al, 2005). Limonene (always more than 87%) was also the major volatile compound of mandarin juices obtained from Philippine Dalandan (Dharmawan, Kasapis, Curran, & Johnson, 2005), Clemenules and Fortuna varieties . Lopez et al (2006) showed that limonene, linalool, a-terpineol and terpinen-4-ol, were considered as quality control parameters in juices processing.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the research conducted on oranges, less information has been reported for other citrus fruits (Tamura et al, 1999;Dharmawan et al, 2007). In addition, few studies comparing volatile components among several citrus species have been performed.…”
Section: Introductionmentioning
confidence: 99%